2013
DOI: 10.1002/esp.3427
|View full text |Cite
|
Sign up to set email alerts
|

Schmidt hammer exposure‐age dating (SHD) of late Quaternary fluvial terraces in New Zealand

Abstract: Schmidt hammer (SH) R‐values are reported for surface clasts from numerically dated Holocene and Pleistocene fluvial terraces in the South Island of New Zealand. The R‐values are combined with previously obtained weathering rind, radiocarbon, terrestrial cosmogenic nuclide and luminescence terrace ages to derive SH R‐value chronofunctions for greywacke clasts from four distinct locations. Our results show that different weathering rates affect the form of the SH R‐value versus Age curve, however a fundamental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 80 publications
1
41
1
Order By: Relevance
“…Rock weathering (and therefore R-values) could have reached saturation in Tierra del Fuego. However, despite agreement that Rvalues will progress toward a dynamic equilibrium over time (White et al, 1998;Engel, 2007;Sánchez et al, 2009;Černá and Engel, 2011;Stahl et al, 2013), numerous studies have effectively distinguished LGM and pre-LGM deposits using the technique on timescales of 10s to 100 s ka (Ballantyne et al, 1997;Rae et al, 2004;Černá and Engel, 2011;Stahl et al, 2013). Very high rates of weathering are required to reduce the ages of the RC 1 boulders (Table 2), yet no obvious jump in R-values occurs between these and the BI 1/BI 2 boulder trains.…”
Section: Rock Surface Weatheringmentioning
confidence: 92%
“…Rock weathering (and therefore R-values) could have reached saturation in Tierra del Fuego. However, despite agreement that Rvalues will progress toward a dynamic equilibrium over time (White et al, 1998;Engel, 2007;Sánchez et al, 2009;Černá and Engel, 2011;Stahl et al, 2013), numerous studies have effectively distinguished LGM and pre-LGM deposits using the technique on timescales of 10s to 100 s ka (Ballantyne et al, 1997;Rae et al, 2004;Černá and Engel, 2011;Stahl et al, 2013). Very high rates of weathering are required to reduce the ages of the RC 1 boulders (Table 2), yet no obvious jump in R-values occurs between these and the BI 1/BI 2 boulder trains.…”
Section: Rock Surface Weatheringmentioning
confidence: 92%
“…Although chemical weathering rates are likely to decline over longer timescales (Colman 1981;Colman & Dethier 1986;Stahl et al 2013;Tomkins et al 2018a, b), near-linear rates can be expected over the Holocene timescale, especially where relatively resistant lithologies are subject to relatively slow rates of chemical weathering in a periglacial environment (Andr e 1996(Andr e , 2002Nicholson 2008Nicholson , 2009Matthews & Owen 2011;. Although chemical weathering rates are likely to decline over longer timescales (Colman 1981;Colman & Dethier 1986;Stahl et al 2013;Tomkins et al 2018a, b), near-linear rates can be expected over the Holocene timescale, especially where relatively resistant lithologies are subject to relatively slow rates of chemical weathering in a periglacial environment (Andr e 1996(Andr e , 2002Nicholson 2008Nicholson , 2009Matthews & Owen 2011;.…”
Section: Calibrated-age Dating Using Shdmentioning
confidence: 99%
“…The same conclusion can be reached from age-calibration curves in the British Isles (Tomkins et al 2018a) and the Pyrenees (Tomkins et al 2018b), which are based on 54 and 52 10 Be TCNDdated granitic surfaces, respectively, all associated with glacial depositional or erosional landforms (moraine boulders or ice-sculpted bedrock). Other studies that have suggested non-linear relationships have involved long timescales and/or have had insufficient control points to test the linearity assumption rigorously over the Holocene timescale (Betts & Latta 2000;S anchez et al 2009;Cern a & Engel 2011;Stahl et al 2013). Other studies that have suggested non-linear relationships have involved long timescales and/or have had insufficient control points to test the linearity assumption rigorously over the Holocene timescale (Betts & Latta 2000;S anchez et al 2009;Cern a & Engel 2011;Stahl et al 2013).…”
Section: Calibrated-age Dating Using Shdmentioning
confidence: 99%
“…The intact rock material is strong to very strong, and unconfined compressive strengths range from 60 to 350 MPa, although rock mass GSI rarely exceeds 60 and is commonly b 5 in zones of major faulting (Richards et al, 2001). Stahl et al's (2013) schmidt hammer testing of Torlesse greywacke clasts indicates that fresh greywacke is relatively homogeneous in strength characteristics across the South Island of New Zealand.…”
Section: Tectonic Setting Geology and Seismic Properties Of The Studmentioning
confidence: 99%